Determination of common urine substances as an assay for improving prostate carcinoma diagnostics - Heger, Zbynek; Cernei, Natalia; Gumulec, Jaromir; Masarik, Michal; Eckschlager, Tomas; Hrabec, Roman; Zitka, Ondrej; Adam, Vojtech; Kizek, Rene (Oncology reports, 2014)
Recently, interest in the identification of non-invasive markers for prostate carcinoma detectable in the urine of patients has increased. In this study, we monitored the abundance of potential non-invasive markers of prostate carcinoma such as amino acid sarcosine, involved in the metabolism of amino acids and methylation processes, ongoing during the progression of prostate carcinoma. in addition, other potential prostate tumor markers were studied. The most significant markers, prostate-specific antigen (PSA) and free PSA (fPSA), already used in clinical diagnosis, were analyzed using an immunoenzymometric assay. Whole amino acid profiles were also determined to evaluate the status of amino acids in patient urine samples and to elucidate the possibility of their utilization for prostate carcinoma diagnosis. To obtain the maximum amount of information, the biochemical parameters were determined using various spectrophotometric methods. All results were subjected to statistical processing for revealing different correlations between the studied parameters. We observed alterations in most of the analyzed substances. Based on the results obtained, we concluded that the specificity of prostate carcinoma diagnosis could be improved by determination of common urine metabolites, since we compiled a set of tests, including the analysis of sarcosine, proline, PSA and uric acid in the urine. These metabolites were not observed in the urine obtained from healthy subjects, while their levels were elevated in all patients suffering from prostate carcinoma.
Keywords: Prostatic Neoplasms; Adenocarcinoma; Uric Acid; nádory prostaty; Chromatography, Liquid; Humans; lidé středního věku; Disease Progression; Proline; Biomarkers, Tumor; Aged; Prostate-Specific Antigen; senioři; lidé; kyselina močová; nádorové biomarkery; chromatografie kapalinová; Male; Middle Aged; prostatický specifický antigen; Aged, 80 and over; sarkosin; senioři nad 80 let; progrese nemoci; adenokarcinom; prolin; mužské pohlaví; Sarcosine